PERAN KEPALA SEKOLAH DALAM MENINGKATKAN MUTU PENDIDIKAN DI SD NEGERI INPRES KOTABARU NABIRE - Laurensia Welikin; Orpasia Madai; Frida Manggaprouw; Adolfina Batkaun; Otolina Belau; Zakmar Makai; Rivaldo Paul Telussa (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze in depth the role of the principal in improving the quality of education through leadership, school management, academic supervision, teacher professional development, improvement of learning quality, relationships with stakeholders, management of facilities and infrastructure, and the development of school culture. This research employs a qualitative approach with a case study design, using data collection techniques through interviews, and is analyzed using an interactive model consisting of data reduction, data display, and conclusion drawing. The results of the study indicate that the principal has implemented leadership in an open, participatory, and contextual manner, which has a positive impact on improving the quality of education, although there are still several challenges that require continuous improvement. Therefore, adaptive and locally grounded principal leadership is a key factor in enhancing the quality of education in the school.